NILAI-NILAI SPIRITUAL, PROFESIONAL DAN HUMANIS PADA KEPEMIMPINAN KEPALA MADRASAH UNGGULAN DI MALANG - Walid, Muhammad (J-PAI: Jurnal Pendidikan Agama Islam, 2019)
Abstract. The emergence of several high-quality and high-quality madrasah in major cities in Indonesia indicates that madrasah is not all inferior. From the above, there is a big question why madrasah can be excellent, but there are also those that are not qualified? Therefore, the existence of superior and good quality madrasah needs to be seen how the leadership of the madrasa head and what is underlying so that it becomes excellent. This study was approached with a qualitative research type of case study. Data was collected through in-depth interviews, semi-involved observations, and documentation. The collected data were analyzed using descriptive qualitative techniques. To measure the validity of the data produced, standards are used; 1) trust, 2) degree of transferability, 3) dependence, and 4) certainty. It can be concluded that the spiritual, professional, and humanitarian values of the madrasa head are much articulated in the processes of managing superior madrasas. The success of the madrasa can be seen how the values and beliefs underlie the head of the madrasa in administering and making madrasas achieve their goals. These values and expectations greatly influence the behavior and practice of leadership, making superior madrassas, ranging from planning to evaluating them, and the procedures that go through them. This is in line with the findings of the literature on transformational spiritualist leadership that these values underlie the principals' leadership practices. The transformational spiritualist school principal delivered his institution towards the vision, mission, and goals with the strongest that spiritual, professional, and humanitarian and educational values were needed.Keywords: Spiritual Value; Professional; Humanist; Featured Madrasah.